Survival of microorganisms on complete dentures following ultrasonic cleaning combined with immersion in peroxide-based cleanser solution - Nishi, Yasuhiro; Seto, Katsura; Kamashita, Yuji; Kaji, Akihito; Kurono, Asutsugu; Nagaoka, Eiichi (Gerodontology, 2014)
Objectives To compare ultrasonic cleaning combined with immersion in a commercially available peroxide‐based cleanser solution (Polident®) with other denture cleaning methods, we examined the quantity of micro‐organisms that survived on dentures before and after various cleaning methods. Subjects and methods One hundred complete dentures belonging to 50 nursing home residents (mean age, 84.6 years) were randomly assigned to five groups according to the cleaning method employed: (A) immersion in Polident® solution alone, (B) brushing with water, (C) ultrasonic cleaning with water, (D) method (A) followed by method (B) and (E) ultrasonic cleaning combined with immersion in Polident® solution. Before and after the dentures had been cleaned, denture biofilm was collected from the mucosal surface of each lateral half of the examined dentures. The collected micro‐organisms were cultured, presumptively identified by standard methods and quantified. Comparisons between the five cleaning methods were carried out using the Kruskal–Wallis test and Dunn's multiple comparisons test. Results The denture cleaning methods involving the use of Polident® solution (methods A, D and E) were significantly more effective at denture disinfection than the other methods (p < 0.05); in particular, the quantity of Candida spp. was lowest after method E (median, 0.00; significantly lower than those observed after methods A, B and C; p < 0.05). Conclusion It was concluded that ultrasonic cleaning combined with immersion in a peroxide‐based cleanser solution effectively reduces the quantity of micro‐organisms surviving on dentures and is a suitable method for elderly individuals who find brushing their dentures difficult.